2005
DOI: 10.1002/jsfa.2193
|View full text |Cite
|
Sign up to set email alerts
|

Screening and construct‐specific detection methods of transgenic Huafan No 1 tomato by conventional and real‐time PCR

Abstract: Genetically modified (GM) tomatoes have been approved for commercialization in many countries since the first GM tomato FLAVR SAVR was permitted for planting in 1994. In China, GM tomato Huafan No 1 with a character of long shelf-life was the first GM plant which was approved for commercialization in 1996. To meet the requirement of the GM tomatoes labeling policy that has been actualized in China since 2001, screening and construct-specific PCR detection methods for detecting the universal elements transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Qualitative and quantitative real-time PCR detection methods were well established for transgenic Huafan No.1 tomato, Bt cottons, MON863 maize, etc. ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative and quantitative real-time PCR detection methods were well established for transgenic Huafan No.1 tomato, Bt cottons, MON863 maize, etc. ( ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that tomatoes with cucumber mosaic virus (CMV) resistance, tobacco mosaic virus (TMV) resistance, increased shelf-life, and cold tolerance have been developed or are under development in China (5,8). CMV is classified into the genus Cucumovirus in the family Bromoviridae and is a plant virus found in most countries (9).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few papers have been published describing the development of a PCR detection method for GM tomato events, such as those for B/Da/F and Huafan No. 1 …”
Section: Introductionmentioning
confidence: 99%
“…1, developed by Huazhong Agriculture University (HZAU) in China, was produced by inserting an expression cassette of anti-sense ethylene-forming enzyme (EFE) gene into the tomato genome with the trait of delayed fruit ripening. 13 To date, only a few papers have been 15,16 In this study, we developed new qualitative and quantitative PCR assays for identification and quantification of GM tomato event Huafan No. 1 based on the cloned 3 flanking sequence of the transgene integration site.…”
Section: Introductionmentioning
confidence: 99%